KEEFEKTIFAN METODE JARIMATIKA TERHADAP HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR DI PURWAKARTA - Diki Nurjana; Rayi Siti Fitriani; Maman Johari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to examine the effectiveness of the Jarimatika (finger-counting) method on the mathematics learning outcomes of fourth-grade elementary school students on multiplication material. A quantitative approach with a quasiexperimental design was employed, involving 52 fourth-grade students of SDN 1 Cibogohilir, Plered, Purwakarta, consisting of 27 students in the experimental class and 25 students in the control class, determined through saturated sampling. Data were collected using pretest and posttest instruments that had been tested for validity and reliability. The pretest results showed no significant difference between the experimental class (mean = 38.48) and the control class (mean = 32.80), asindicated by an Independent Samples t-test (Sig. = 0.792 > 0.05), confirming that both groups had equivalent initial abilities. After treatment, the posttest mean of the experimental class (81.59) was far higher than that of the control class (37.40). Because the posttest data were not normally distributed, the Mann-Whitney U test was applied and produced a significance value of 0.000 (< 0.05), indicating a significant difference in learning outcomes between the two groups. The effect size analysis using Cohen's d yielded a value of 2.69, categorized as a large effect. These findings indicate that the Jarimatika method is highly effective in improving students' understanding of multiplication concepts and can be recommended as an alternative learning strategy for elementary mathematics teachers.